Energy Auditing at Block 1 Muara Karang Combined Cycle Power Plant - Andy Setyanto; Ary Bachtiar Krishna Putra (Institut Teknologi Sepuluh Nopember, 2018)
Every year electricity growth in the world always increases. But the growing growth is the need for future controls in order to make the utilization more effective and efficient. In addition, with the utilization of appropriate energy will have an impact on the preservation of the surrounding environment. In Indonesia, has been regulated related to the efficient utilization of energy by the enactment of Government Regulation No 70 of 2009 of Energy Conservation. The method used for this research is to conduct an energy audit on PLTGU Block 1 Combined Cycle Power Plant (CCPP) Muara Karang. This audit is begin from collecting operating parameters’ data then conducting the performance calculation of the main equipment. The result of the calculation then compared with commissioning data in 1995. From the calculation obtained the profile of energy use and find the largest gap from the comparison between actual performance with commissioning in 1995. The gap is then analyzed the cause of equipment inefficiency and conducted field study. After that is given the recommendation of Energy Saving Potential to be able to improve the efficiency of the equipment. The recommendations are analyzed by economic studies to provide alternative improvements solution for management.